Patients' pre-treatment interpersonal problems as predictors of therapeutic alliance in long-term psychodynamic psychotherapy. (30th July 2016) - Ollila, Pekka; Knekt, Paul; Heinonen, Erkki; Lindfors, Olavi
Abstract: Information on how the patient's interpersonal problems predict alliance development during long-term therapy is lacking. The aim of this study was to explore how the patient's pre-treatment interpersonal problems predict the development of alliance in long-term psychotherapy. Altogether 128 adult outpatients experiencing mood or anxiety disorder were assigned to long-term psychodynamic psychotherapy in the Helsinki Psychotherapy Study. The Inventory of Interpersonal Problems (IIP) total score and the eight octant scores, assessed at baseline, were used as predictors. The trajectories of change in patient- and therapist-rated Working Alliance Inventory (WAI) were used as outcome measures at 7, 12, and 36 months of follow-up after baseline. Study of the changes by time showed that the patient-rated alliance was significantly improved by the 36-month follow-up, i.e. the most usual end-point of therapy, in persons with higher pre-treatment level of the IIP total score. Low total IIP score and low to moderate level of hostile type problems showed no slope of improvement of patient-rated alliance during follow-up. The therapist-rated alliance showed a similar course as the patient-rated alliance with the exception of a faster improvement for higher IIP scores. In conclusion, a higher level of patients' interpersonal problems predicted favorable alliance development. Highlights: The more interpersonal problems were reported, the more the alliance improved. The association between initial interpersonal problems and alliance was strongest at the end of therapy. Long-term therapy can establish a new corrective relational experience.